Tetracyanoquinodimethane reduction by complexed guanidinyl-functionalized aromatic compounds - Herrmann, Hendrik Hans; Ziesak, Alexandra Sabrina; Wild, Ute; Leingang, Simone; Schrempp, David; Wagner, Norbert; Beck, Johannes; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (ChemPhysChem, 2014)
In this work, we report on the reduction of tetracyanoquinodimethane (TCNQ) with dicationic complexes of guanidinyl-functionalized aromatic (GFA) electron donors. In contrast to reduction with free GFAs, milder reduction conditions were achieved, and this led to semiconducting materials with extended TCNQ π stacking. The charge on the TCNQ units was estimated from the structural data obtained by single-crystal X-ray diffraction analysis and from IR spectroscopic data. The electrical conductivity was studied and the activation energy of the semiconducting materials was estimated from the temperature dependence of the conductivity.